2022
DOI: 10.1128/jvi.00509-22
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Assessment of SARS-CoV-2-Specific T Cell Cytokine-Producing Responses for 1 Year Reveals Persistence of Multicytokine Proliferative Responses, with Greater Immunity Associated with Disease Severity

Abstract: Our findings highlight the relative importance of SARS-CoV-2-specific GzmB-producing T cell responses in SARS-CoV-2 control and shared CD4 and CD8 immunodominant epitopes in seasonal coronaviruses or SARS-CoV-1, and they indicate robust persistence of T cell memory at least 1 year after infection. Our findings should inform future strategies to induce T cell vaccines against SARS-CoV-2 and other coronaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 60 publications
4
16
0
Order By: Relevance
“…Overall, our research suggests that while there is a decline in antibody titres, the memory T cells should render longer‐lasting protective effects. This notion is supported by other groups, who also observed long‐lasting T‐cell responses 61,62 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, our research suggests that while there is a decline in antibody titres, the memory T cells should render longer‐lasting protective effects. This notion is supported by other groups, who also observed long‐lasting T‐cell responses 61,62 …”
Section: Discussionsupporting
confidence: 80%
“…This notion is supported by other groups, who also observed long-lasting T-cell responses. 61,62 Three individuals in our cohort, HH-SP-02, HH-SP-04 and HH-SP-05, were immunosuppressed because they either received immunosuppressive medication or chemotherapy. Despite a dysfunctional B-cell response indicated by a negative nucleocapsid and spike antibody titres for HH-SP-02 and HH-SP-04, they showed substantial spike-specific CD4 + T-cell responses with 16 and 19 recognised peptide specificities, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a significant correlation between T-cell activation and protection from infection, although our study might have been underpowered to detect this effect due to the small sample size of the T-cell cohort. Studies published between 2021 and 2022 showed high SARS-CoV-2-specific T-cell activation following severe disease 21 and impaired protection from infection in rhesus macaques ( Macaca mulatta ) following CD8 T-cell depletion, 22 suggesting that cellular immunity can contribute to protection against SARS-CoV-2. It was proposed that memory T cells might protect populations from severe infections, 23 , 24 perhaps when antibody titres are waning.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + and CD8 + cells exhibit complex cytokine secretion and regulation dynamics. Recent studies on SARS-CoV-2 infection in humans have shown that cytokines are primarily produced by CD4+ cells, and that CD8+ are suppressed throughout the course of infection 12,93 . Here, we consider a simplified approach where IFN-γ and Interleukin (I) cytokine production by primed CD4 + cells.…”
Section: Model For In-host Mrna Vaccinationmentioning
confidence: 99%